WAVE ENERGY CONVERTER SYSTEM ANALYSIS PERFORMANCE WITH PITCH MOTION IN VARIOUS DIMENSIONS AND DRAFT FOR APPLIED IN INDONESIA SEA - Muhammad Fahmi (Indonesian Journal of Multidisciplinary Science, 2022)
In Indonesia, national electricity consumption is expected continue to rise every year. One solution to meet the needs of electrical energy is to use clean energy that is sustainable to environment. Seeing Indonesia as an archipelagic country, One of renewable energy that could develop is ocean energy (Wave Energy Converter). Wave Energy Converter can be converted into electrical energy through a converter in the form of a floating structure. The structure will respond to the external force of the ocean waves into the pitching motion. The pitch movement will move a series of tools which are then channeled into a generator to produce electrical energy. The structure is said to be effective if it produces a large enough performance value. In this study the structure is modeled with various drafts and dimensions to obtain the most optimal hydrostatic parameter values. Furthermore, from this value, it is possible to estimate the amount of electrical energy that can be generated by adding a uniformed PTO damping value for each structure. From the results of the study, it was found that each structure with the same PTO damping value of 5×104kNm has a different performance value in each wave period. From the results of the analysis, it is found that the greater the value of mass and radiation damping, the greater the energy generation and performance of the structure. The structure that has the best performance is structure-6 with a Performance value of 72.12% at a wave period of 9 seconds which match with North Sumatera mean wave period.